Taxing the income from U.S. corporation investments abroad - Brownlee, Oswald H. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1979)
The book summarizes current knowledge about effects of taxing the foreign investment income of U.S. corporations.
Includes bibliographical references: p. 33-34.
osc 04/07/2017
Loans
Keywords: Corporations; Income tax; Investments, American